Analyze of Influencer Strategies @wipangs through Endorsement on Immoderma Brand - Risqi Herawan, Alif Nur annisa; Hapsari, Swita Amallia (Program Studi Ilmu Komunikasi FBIK Unissula, 2025)
AbstractNowadays, communication technology has become a primary channel for delivering information, especially in the business sector. Consequently, the use of social media has become a promotional medium that is considered impactful. One strategy involves selecting influencers who can engage the audience and encourage them to follow all recommended information. In Semarang, one beauty influencer, @wipang, is recognized for her unique approach to marketing products through endorsement collaborations. The brand Immoderma, which employs Wipang as an influencer, has developed a content-based partnership strategy. This study describes the beauty clinic brand in Semarang, Immoderma, which chooses influencers as a promotional strategy through endorsement collaborations. The researcher employs a qualitative descriptive research method, utilizing Integrated Marketing Communication (IMC) theory and an endorsement model concept that includes expertise, popularity, and reputation. To gather data, the researcher conducts interviews with Wipang as the primary data source. For secondary data, the researcher uses observation and documentation. The findings indicate that selecting an influencer as a promotional strategy through endorsement collaborations can effectively capture the public's attention for the Immoderma brand.Keywords: Endorsment; Influencer; Instagram;Wipang